Review on the development of wing-in-ground crafts - Md Zhahir, Md Amzari; Ahmad, Mohamed Tarmizi; Abdul Hamid, Mohd Faisal; Gires, Ezanee; Hassan, Aziz (EDP Sciences, 2024)
This paper focuses on the development of Ground Effect Craft (GEC). The ultimate objective of this paper is to comprehensively outline all publicly disclosed and well-known GECs. The scope of this paper encompasses a review of the design challenges and architectures associated with GECs that have been prevalent for more than 60 years. It delves into research, development, and enhancements of existing GECs throughout their history. In conclusion, considering current technological advances, GECs present substantial opportunities and potential to evolve into a viable mode of transportation, effectively bridging the gap between aircraft and ships. The incentive to overcome the economic challenges associated with fabricating and operating GECs is worthwhile, encouraging exploration and development toward a commercially viable GEC.